The role of a conserved tyrosine residue in high-potential iron sulfur proteins. - Iwagami, S. G. (Cold Spring Harbor Laboratory Press, 1995)
Conserved tyrosine-12 of Ectothiorhodospira halophila high-potential iron sulphur protein (HiPIP) iso-I was substituted with phenylalanine (Y12F), histidine (Y12H), tryptophan (Y12W), isoleucine (Y12I), and alanine (Y12A). Variants Y12A and Y12I were expressed to reasonable levels in cells grown at lower temperatures, but decomposed during purification. Variants Y12F, Y12H, and Y12W were substantially destabilized with respect to the recombinant wild-type HiPIP (rcWT) as determined by differential scanning calorimetry over a pH range of 7.0-11.0. Characterization of the Y12F variant by NMR indicates that the principal structural differences between this variant and the rcWT HiPIP result from the loss of the two hydrogen bonds of the Tyr-12 hydroxyl group with Asn-14 O delta 1 and Lys-59 NH, respectively. The effect of the loss of the latter interaction is propagated through the Lys-59/Val-58 peptide bond, thereby perturbing Gly-46. The delta delta GDapp of Y12F of 2.3 kcal/mol with respect to rcWT HiPIP (25 degrees C, pH 7.0) is entirely consistent with the contribution of these two hydrogen bonds to the stability of the latter. CD measurements show that Tyr-12 influences several electronic transitions within the cluster. The midpoint reduction potentials of variants Y12F, Y12H, and Y12W were 17, 19, and 22 mV (20 mM MOPS, 0.2 M sodium chloride, pH 6.98, 25 degrees C), respectively, higher than that of rcWT HiPIP. The current results indicate that, although conserved Tyr-12 modulates the properties of the cluster, its principle function is to stabilize the HiPIP through hydrogen bonds involving its hydroxyl group and electrostatic interactions involving its aromatic ring.